Interpersonal Meaning of Motivational YouTube Video Headlines - Alifia Sabilla Yasmin; Iwa Lukmana; Riesky Riesky (Passage, 2019)
YouTube has now become one of the most successful video-sharing platforms used by many people around the world. It seems that one of the reasons why people tend to choose YouTube rather than any other video-sharing platform is the attractive headline. This study aims to reveal the realization of interpersonal meaning in YouTube video headlines and to reveal the realization of interpersonal meaning in different types of headlines. This study is largely qualitative supported by descriptive quantification. The data include a hundred headlines collected from Jay Shetty’s channel on YouTube. In order to find out the realization of interpersonal meaning, the headlines are categorized based on the speech function and its typicality proposed by Halliday and Matthiessen (2014). The headlines are also categorized by using Maslen’s (2010) types of headlines. There are two findings of this study. Firstly, four initiating speech functions are realized in Jay Shetty’s headlines namely statement, question, command, and offer. The dominant speech function found in this study is offer, which is realized untypically in the imperative mood. Secondly, the dominant type of headlines found in this study is the headlines that arouse the curiosity of the readers. This type of headline appears in all of the speech functions found in this study.Keywords: Interpersonal meaning; speech function; types of headlines; typicality.